Criteria and indexes of readiness formation of the future engineer-teacher to use healthsaving technologies. - Lukyanova Ju.S (Kharkov National Pedagogical University, 2011)
Clarified the basic criteria and indexes that reflect changes in the availability of future engineers and educators to use healthsaving technology: motivational-axiological (relevance to human health as a value, an interest in using healthsaving technologies); personal (forming communicative and reflective qualities); epistemological (knowledge about the basic of formation students' health saving); operation (formation of designing and organizational skills of the educational process that has a healthsaving character).